Pengharaman Khamr dalam Al-Qur’an (Studi atas Tafsir Tarjuman Al-Mustafid Karya Abd. Rauf As-Sinkili) - Muhafizah el-Feyza; M. Riyan Hidayat (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
This paper describes the prohibition of khamar in the Qur'an. As we know, the abuse of khamar is now not only limited to people whose economy is peaking, but also to the underprivileged, not only among non-students, but also students. Reflecting on this, if it continues to be allowed, it will damage from generation to generation due to the abuse of khamar. Therefore, it is important for us to know how the prohibition of khamar in the Qur'an. The purpose of this study is to find out how the interpretation of the verses about the process of prohibiting khamar in Tarjuman Mustafid's interpretation so that it can increase knowledge in the current era. This research uses qualitative research with descriptive-analytic approach. The results of this paper are based on the interpretation of Abd. Rouf As-Sinkili that the prohibition of khamar begins with the presence of fruits that can be used as khamar to become haram, but there are also those that make it a useful drink until it becomes halal. Then, it is explained that in khamar there are big and small dangers of benefit, in the next stage Allah forbids drinking khamar only during prayer, and then khamar is absolutely forbidden because consuming it is a big sin.